SCALE UP PENDAPATAN PEMANFAATAN LIMBAH HASIL PENGGILINGAN PADI - Muhamad Rochman; Retno Kusuma Ningsih; Jeni Susyanti (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2023)
This activity aims to improve the quality of rice husk charcoal products and market access for farmer groups. The project identified key problems faced by farmer groups, particularly related to ineffective product packaging. Using the implementation of socialization, counseling, training, and evaluation we provide training on husk product processing, designing more efficient packaging, and providing guidance on environmentally friendly product practices. The results of this activity include improving the quality of rice husk charcoal products, increasing the income of farmer groups, and wider market access. Product quality improvement is achieved through technical training that includes raw material selection, efficient burning, and proper packaging. Better packaging has opened the door to a wider market, allowing farmer groups to get better selling prices. The sustainable approach also promotes environmentally friendly products in the production of rice husk charcoal. Overall, these community service activities have provided tangible benefits to farmer groups, increased their incomes and sustainability of their agricultural businesses, and provided valuable lessons on community-based approaches and sustainable support in agricultural business development.